Alterations in microbiota and their metabolites are associated with beneficial effects of bile acid sequestrant on icteric primary biliary Cholangitis. (1st January 2021) - Li, Bo; Zhang, Jun; Chen, Yong; Wang, Qixia; Yan, Li; Wang, Rui; Wei, Yiran; You, Zhengrui; Li, Yikang; Miao, Qi; Xiao, Xiao; Lian, Min; et al.
ABSTRACT: Background : Increasing data suggests an interaction between bile acids and intestinal microbiota in the pathogenesis of primary biliary cholangitis (PBC). Bile acid sequestrants are widely used to bind bile acids in the intestinal lumen and are therefore posited to impact gut bacteria. Herein we aimed to investigate the effects of cholestyramine on the bile acid profile and gut microbiome in a cohort of icteric PBC patients. Results: Thirty-three PBC patients were treated with cholestyramine, serum and stool samples were collected at baseline, 4 and 16 weeks. Shotgun metagenomic sequencing and targeted metabolomic profiling were performed. Following cholestyramine administration, patients exhibited a high interpersonal variability in remission of cholestasis, and were therefore dichotomized according to the decrease of total bilirubin. Gut microbial co-abundance networks showed distinct taxa interactions between subjects with superior remission (SR) and those with inferior remission (IR) at baseline. After treatment, compositional shifts of the microbiome in the SR group were characterized with enrichment of two Lachnospiraceae species, typically producing short-chain fatty acids (SCFAs). In contrast, Klebsiella pneumonia, a commensal pathobiont, was only increased in the IR group. Correspondingly, metabolome analysis demonstrated that patients with SR, but not IR, were marked by elevations of SCFAs including valeric acid and caproic acid. Finally, integrative analysis identified robust associations between the variations of microbiota, metabolites, and inflammatory cytokines in SR group, indicating potential mechanistic links. Conclusions: Beneficial responses caused by cholestyramine were closely related with compositional and functional alterations in gut commensal, highlighting the possibility of exploring bile acid-microbiota interactions for treating PBC.